OUR EXPERIENCE IN TREATMENT OF ENTEROATMOSPHERIC FISTULAS FORMED AS A RESULT OF MINE-EXPLOSIVE INJURY - Kyrylo Parkhomenko; Anastasia Drozdova; Kostiantyn Prokopenko; Ivan Parkhomenko (Acta Medica Leopoliensia)
A mine-explosive injury is a special type of injury, and in most cases, the surgeon encounters a victim with polytrauma, including an injury to the organs of the abdominal cavity. However, 87% of all penetrating wounds of the abdominal cavity are accompanied by intestinal damage, which in the future can lead to the formation of enteroatmospheric fistulas.